Piperine Inhibits TGF-β Signaling Pathways and Disrupts EMT-Related Events in Human Lung Adenocarcinoma Cells - Leonardo Marques da Fonseca; Lucas Rodrigues Jacques da Silva; Jhenifer Santos dos Reis; Marcos André Rodrigues da Costa Santos; Victoria de Sousa Chaves; Kelli Monteiro da Costa; Julliana de Nazareth Sa-Diniz; Celio Geraldo Freire de Lima; Alexandre Morrot; Tatiany Nunes Franklim; Douglas Chaves de Alcântara-Pinto; Marco Edilson Freire de Lima; et al. (Medicines, 2020)
Background: Piperine, an amide extracted from the Piper spices, exhibits strong anti-tumor properties. However, its effect on the epithelial–mesenchymal transition (EMT) process has never been investigated. Herein, we evaluate the toxic effect of piperine on lung adenocarcinoma (A549), breast adenocarcinoma (MDA-MB-231) and hepatocellular carcinoma (HepG2) cell lines, as well as its ability to inhibit EMT-related events induced by TGF-β1 treatment. Methods: The cell viability was investigated by MTT assay. Protein expression was evaluated by Western blot. Gene expression was monitored by real-time PCR. Zymography assay was employed to detect metalloproteinase (MMP) activity in conditioned media. Cell motility was assessed by the wound-healing and phagokinetic gold sol assays. Results: The results revealed that piperine was cytotoxic in concentrations over 100 µM, showing IC50 values for HepG2, MDA-MB-231 and A549 cell lines of 214, 238 and 198 µM, respectively. In order to investigate whether piperine would reverse the TGF-β1 induced-EMT, the A549 cell line was pretreated with sublethal concentrations of the natural amide followed by the addition of TGF-β1. Besides disrupting EMT-related events, piperine also inhibited both ERK 1/2 and SMAD 2 phosphorylation. Conclusions: These results suggest that piperine might be further used in therapeutic strategies for metastatic cancer and EMT-related disorders.